Data mining and knowledge discovery for geoscientists - Shi, Guangren (Elsavier, 2014)
"In the early 21 century, data mining (DM) was predicted to be "one of the most revolutionary developments of the next decade," and chosen as one of 10 emerging technologies that will change the world (Hand et al., 2001; Larose, 2005; Larose, 2006). In fact, in the recent 20 years, the field of DM has seen enormous success, both in terms of broad-ranging application achievements and in terms of scientific progress and understanding. DM is the computerized process of extracting previously unknown and important actionable information and knowledge from database (DB). This knowledge can then be used to make crucial decisions by leveraging the individual's intuition and experience to objectively generate opportunities that might otherwise go undiscovered"--
Includes bibliographical references and index.
Keywords: Geology; Data mining